2009
DOI: 10.15394/jdfsl.2009.1059
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hard Disk Firmware Steganography on Computer Forensics

Abstract: The hard disk drive is probably the predominant form of storage media and is a primary data source in a forensic investigation. The majority of available software tools and literature relating to the investigation of the structure and content contained within a hard disk drive concerns the extraction and analysis of evidence from the various file systems which can reside in the user accessible area of the disk. It is known that there are other areas of the hard disk drive which could be used to conceal informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Du, Ledwith and Scanlon (2018) further back up Laurenson (2016) and compared several forensic tools, finding that they did not scan the firmware of disks. Sutherland et al (2009) used well-known forensic software Encase, FTK and AccessData. They found that changing the error lists in the firmware was not detected by any of the software tested.…”
Section: Attacks Against Forensics Tools and Processesmentioning
confidence: 99%
“…Du, Ledwith and Scanlon (2018) further back up Laurenson (2016) and compared several forensic tools, finding that they did not scan the firmware of disks. Sutherland et al (2009) used well-known forensic software Encase, FTK and AccessData. They found that changing the error lists in the firmware was not detected by any of the software tested.…”
Section: Attacks Against Forensics Tools and Processesmentioning
confidence: 99%
“…Any flaws identified on the drive during production are recorded in the disk firmware as the 'P' (primary, production or permanent) list. As the disk ages and as a result of wear & tear other sectors fail and this is recorded within the firmware area in the 'G' (growth) list [6,7]. Reads and writes are automatically redirected (remapped) to spare sectors within the Reserved Area (see Fig.…”
Section: Hard Drive Firmware Functionalitymentioning
confidence: 99%